The (re)construction of history through fictional and non-fictional narratives: Hotel Rwanda and Rwanda’s Untold Story - Mudzingwa, Munashe (Midlands State University, 2017)
This study is about the construction and reconstruction of ‘reality’ in fictional and non-fictional films Hotel Rwanda (George, 2004) and Rwanda’s Untold Story (Terry, 2014). The study explores, and explains how cinematographic and narrative techniques are used to (re)construct the history of the Rwanda genocide. Political Economy of Film and the Gaze theory were employed to provide a theoretical base for this research. The study employed qualitative research methods, archival research and critical discourse analysis to collect and analyse data. Among other things, the study found out that both filmic accounts have a predominant Western gaze. In Hotel Rwanda Africa is viewed as a continent of chaos, corruption and senseless barbarity through the massacres and corruption that is dramatized therein. In Rwanda’s Untold Story, Rwanda is described as a country dominated by its dark history and the genocide is described as senseless barbarity. The study recommends ‘African’ filmmakers to start making films that deconstruct the colonial gaze.